FORMALITY IN INDONESIAN TALK SHOWS: Differences between hitam putih and bukan empat mata talk show - Anysawardhani, Agistya Nilam (2015)
This research investigates the use of formality by using formality measurement or F-score proposed by Heylighen & Dewaele (1999) in the talk show's situation which is focused on host's utterances. Mixed method is used in examining level of formality on Bukan Empat Mata and Hitam Putih talk shows. The research uses two episodes from each talk show which have similarity in topic and guest stars. The findings reveal three main points. First, Bukan Empat Mata has the higher score of formality than Hitam Putih. Second, personality factors that are level of education and introversion influence in formality. Third, the use of informal language in Indonesian context is found and it is also calculated in order to support in the determining of level of formality. The result of the calculation means that the result is significant. Keywords: formality, F-score, Indonesian talk shows, level of education, introversion ---------- Penelitian ini meneliti penggunaan formalitas dengan menggunakan pengukuran formalitas atau F-score yang dikemukakan oleh Heylighen & Dewaele (1999) dalam situati talk show yang difokuskan pada ujaran pembawa acara. Metode campuran digunakan dalam pengujian tingkat formalitas pada talk show Bukan Empat Mata and Hitam Putih. Penelitian ini menggunakan dua episode dari masing - masing talk show yang mana memiliki kesamaan dalam topik dan bintang tamu. Hasil pememuan menyatakan tiga poin penting. Pertama, Bukan Empat Mata memiliki nilai formalitas paling tinggi dibandingkan dengan Hitam Putih. Kedua, faktor kepribadian yaitu tingkat pendidikan dan introversi mempengaruhi formalitas. Ketiga, penggunaan bahasa tidak baku pada konteks bahasa Indonesia ditemukan dan dihitung untuk mendukung penentuan tingkat formalitas. Hasil penghitungan menyatakan bahwa hasilnya signifikan.